Molecular characterization of denitrifying Bacteria and their potential In reduction Of nitrogenous Compounds In Lake Victoria, Kenya - Wachira, James Murimi (UoEm, 2023)
Nutrient loading with nitrogen and phosphorus in receiving waters is an increasing concern worldwide. In Lake Victoria basin, the substantial inflow of nutrients has led to extensive eutrophication which has resulted in the reiterative proliferation of invasive species of aquatic weeds like water hyacinth and cyanobacteria in the Lake Victoria basin hence causing mass mortality of fish and health risks. Nowadays, anthropogenic activities such as crop production, sewage discharge, fossil fuel combustion and fertilizer use have substantial intensified, therefore increasing the amount of nitrogen entering into terrestrial ecosystems. Heterotrophic nitrification and aerobic denitrification have been proposed as alternate strategies in nitrogen reduction in nitrogen-rich ecosystems. In this study, we examined the diversity of bacteria involved in nitrogen cycling and their potential application in bioremediation in Lake Victoria. Eight water samples were collected in triplicate using 500 ml sterile bottles and taken to SGS Kenya Limited Laboratory Services for physiochemical analysis. Total bacterial diversity in the collected samples was assessed using universal primers. Purified DNA (25 μl) was stabilized using DNAstable® (Biomatrica), air-dried, followed by Illumina sequencing. A culture dependent approach was used to recover aerobic denitrifiers using a medium with (NH4)2SO4 as the main N source in Bromothymol blue medium (BTB). Serial dilution was done and spread plated onto the BTB media followed by incubation. Single isolates were selected from the plates and sub-cultured in a similar media to obtain pure cultures. Screening for Nitrogen removal was done by inoculating single colony into screening medium containing (NH4)2SO4 as the main N source. Selected pure cultures were presumptively characterized based on molecular tests. Molecular characterization was achieved by extracting the DNA of positive isolate, amplifying 16S rRNA gene using universal primers (515F/806R), and sequencing. In order to determine how much nitrogen (N) was removed from effluent samples, 50 ml of sterilized wastewater was inoculated with a single colony and incubate at 30 °C for 120 hours and 150 rpm. Nitrogen removal by isolates was quantified using a spectrophotometer. Low absorbance indicated fewer molecules available to interact with the light, and vice versa. Physiochemical analysis showed there were elevated levels of total nitrogen and ammonia in both treated and untreated WWTPs as compared to lake and rivers samples. The sequence reads were grouped into 1,763 operational taxonomic units (OTUs). There OTUs were affiliated to 26 bacterial phyla with Proteobacteria being the most dominant phylum. Microbial diversity increased from WWTPs, rivers to lake. Isolated positive for nitrogen removal were recovered from the lake and WWTPs ecosystems and none from the river samples. The isolates were affiliated to genera Pseudomonas, Klebsiella, and Enterobacter in the phylum Proteobacteria. Klebsiella quasivariicola showed the highest utilization of nitrate and ammonium from the basal media as indicated by low absorbance values of 95.32% and 93.18%. The findings from this study show that bacteria play a very important role in removal of nitrogenous waste from waste water and some of them can be used in bioremediation efforts.
Keywords: Reduction Of Nitrogenous Compounds